RISK ASSESSMENT AND SAFETY MEASURES IN MODERN NUCLEAR POWER PLANTS: BALANCING INNOVATION AND PUBLIC TRUST - Ziyadullaev Abdukakhar Shamsievich (Western European Studies, 2024)
Modern nuclear power plants are central to global efforts to transition toward lowcarbon energy systems, but safety concerns remain a critical challenge to their widespread acceptance. This article explores the methodologies of risk assessment and the implementation of advanced safety measures in nuclear power plants. It examines technological innovations, regulatory frameworks, and case studies to highlight the industry's efforts in minimizing risks and enhancing public trust. While advancements such as passive safety systems and digital monitoring tools improve reliability, transparent communication and public engagement are vital to overcoming societal apprehensions
Keywords: Nuclear power; risk assessment; safety measures